Residual Tumor Volume and Tumor Progression after Subtotal Resection and Observation of WHO Grade I Skull Base Meningiomas - Przybylowski, Colin J.; Hendricks, Benjamin K.; Furey, Charuta G.; DiDomenico, Joseph D.; Porter, Randall W.; Sanai, Nader; Almefty, Kaith K.; Little, Andrew S. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective This study investigated the impact of residual tumor volume (RTV) on tumor progression after subtotal resection and observation of WHO grade I skull base meningiomas.Study Design This study is a retrospective volumetric analysis.Setting This study was conducted at a single institution.Participants Patients who underwent subtotal resection of a WHO grade I skull base meningioma and postsurgical observation (July 1, 2007–July 1, 2017).Main Outcome Measure The main outcome was radiographic tumor progression.Results Sixty patients with residual skull base meningiomas were analyzed. The median (interquartile range) RTV was 1.3 (5.3) cm3. Tumor progression occurred in 23 patients (38.3%) at a mean duration of 28.6 months postsurgery. The 1-, 3-, and 5-year actuarial progression-free survival (PFS) rates were 98.3, 58.6, and 48.7%, respectively. The Cox multivariate analysis identified increasing RTV (p = 0.01) and history of more than 1 previous surgery (p = 0.03) as independent predictors of tumor progression. In a Kaplan–Meier analysis for PFS, the RTV threshold of 3 cm3 maximized log-rank testing significance between groups of patients dichotomized at 0.5 cm3 thresholds (p < 0.01). The 3-year actuarial PFS rates for meningiomas with RTV ≤3 cm3 and >3 cm3 were 76.2 and 32.1%, respectively. When RTV >3 cm3 was entered as a covariate in the Cox model, it was the only factor independently associated with tumor progression (p < 0.01).Conclusion RTV was associated with tumor progression after subtotal resection of WHO grade I skull base meningioma in this cohort. An RTV threshold of 3 cm3 was identified that minimized progression of the residual tumor when gross total resection was not safe or feasible.
Keywords: meningioma; progression; recurrence; residual; skull base; tumor